2009
DOI: 10.1080/01635580802348658
|View full text |Cite
|
Sign up to set email alerts
|

Meat Consumption, Heterocyclic Amines, NAT2, and the Risk of Breast Cancer

Abstract: Meat consumption and heterocyclic amine (HCA) intake have been inconsistently associated with breast cancer risk in epidemiologic studies. Genetic variation in N-acetyltransferase2 (NAT2) has been suggested to modify the association of meat intake with breast cancer through its influence on metabolism of HCAs. We examined associations between meat intake, HCA exposure, acetylator genotype, and breast cancer risk in a case-control study of 2,686 case women and 3,508 controls. Women were asked to report their us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 44 publications
2
10
0
1
Order By: Relevance
“…Our finding for red meat was consistent with the previous nested case-control studies in the NHS (14), Iowa Women’s Health Study (16), and population-based case-control studies with over 1000 cases (12, 13). In our study, 26% of the cases were also included in the previous study in the NHS (14).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding for red meat was consistent with the previous nested case-control studies in the NHS (14), Iowa Women’s Health Study (16), and population-based case-control studies with over 1000 cases (12, 13). In our study, 26% of the cases were also included in the previous study in the NHS (14).…”
Section: Discussionsupporting
confidence: 91%
“…The study used a comprehensive 192-item FFQ with a total of 63 foods and recipes in the FFQ to cover intake of individual meat items and mixed-dishes containing meat. For individual HCAs and MDM intake, few studies have examined the interaction with NAT 2 genotype, and no interactions between either HCAs (12, 15) or MDM (12) and NAT2 genotype were found on breast cancer risk, consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported that PhIP DNA adduct levels in human breast tissue are higher in rapid than slow NAT2 acetylators (Zhu et al, 2003) and have suggested that rapid acetylator NAT2 phenotype increases colorectal (Lang et al, 1994; Chen et al, 1998; Le Marchand et al, 2001; Lilla et al, 2006; Ognjanovic et al, 2006; Cotterchio et al, 2008), breast (Deitz et al, 2000; Gallicchio et al, 2006), and lung (Chiou et al, 2005) cancer risk in individuals exposed to heterocyclic amine carcinogens. In contrast, other studies carried out with colorectal (Barrett et al, 2003; Barlak et al, 2006), breast (van der Hel et al, 2004; Ochs-Balcome et al, 2007; Mignone et al, 2009), and lung (Barlak et al, 2006) cancer do not support the association with rapid acetylator NAT2 phenotype. A much more robust effect of NAT2 phenotype has been noted for mutagenicity and DNA adduct formation from 2-amino-3,8-dimethylimidazo-[4,5-f]quinoxaline (MeIQx) (Bendaly et al, 2007).…”
Section: Discussionmentioning
confidence: 84%
“…b P trend calculated using the median of each quintile. Mignone et al, 2009). Interactions between meat (Zheng et al, 1999;Egeberg et al, 2008) or well-done meat (Zheng et al, 1999;Deitz et al, 2000) and xenobiotic-metabolising gene variants might explain these contradictory findings.…”
Section: Discussionmentioning
confidence: 96%
“…Iron may also be involved in breast cancer through interaction with catechol oestrogen metabolites or production of hydroxyl radicals (Liehr and Jones, 2001;Huang, 2003;. Limited epidemiological studies of meat mutagens (De Stefani et al, 1997;Delfino et al, 2000;Sinha et al, 2000;Steck et al, 2007;Sonestedt et al, 2008;Kabat et al, 2009;Mignone et al, 2009) and haem iron (Lee et al, 2004; are inconsistent.…”
mentioning
confidence: 99%